Analysis of Students’ Critical Thinking Skill of Middle School through STEM Education Project-Based Learning - Mutakinati, L.; Anwari, I.; Kumano, Y. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
This research is to investigate the students` critical thinking skill by using STEM education through Project Based Learning. The study applied descriptive research design. In these lessons, the participants were 160 first grade Japanese middle school students from four classes. They were divided into nine groups each class. The instruments are worksheets to explore studentsÃ¢â‚¬â„¢ initial knowledge about how to clean up wastewater and critical thinking processes. The worksheet consists of the designing solution, and understanding of concepts to identify critical thinking based on purpose and question, selection of information, assumption, and point of view the solution, and implication. Students were asked to design tools to clean up the wastewater. Students were given more than one chance to design the best product for wastewater treatment. The lessons consist of six lessons. The first lesson is the introduction of colloid, solution, and suspension, and discussion about wastewater. The second lesson to the fourth lesson was finding solutions and designing products. The fifth lesson was to watch a video of wastewater treatments in Japan and to optimize the solutions or products. The last lesson was to make a conclusion, to exchange presentations, and to develop discussion. Implementation of STEM education can be seen from the students` solutions, some students used biology or chemistry or physics or combination concept and Mathematics to design solution (technology) for treatment of wastewater. The result showed that the mean score of students` critical thinking skill was 2.82. The students` critical thinking skill was categorized as advanced thinker: 41.6%, practicing thinker: 30,6%, beginning thinker: 25%, and challenged thinker: 2.8%.Ã‚Â And the category for students` critical thinking was practicing thinker.Ã‚Â Practicing thinker is a stage of critical thinking development, they have enough skill in thinking to critique their own plan for systematic practice, and to construct a realistic critique of their powers of thought to solve the contextual problem.